Analogues of dealanylalahopcin are inhibitors of human HIF prolyl hydroxylases. - Schlemminger, I; Mole, D; McNeill, L; Dhanda, A; Hewitson, K; Tian, Y; Ratcliffe, P; Pugh, C; Schofield, C (2003)
Analogues of the naturally occurring cyclic hydroxamate dealanylalahopcin, which is an inhibitor of procollagen prolyl-4-hydroxylase, were synthesised and shown to be inhibitors of the human hypoxia-inducible factor prolyl hydroxylases.